Tree health in near pristine, heavily invaded and restored riparian zones : the role of pests and fungal pathogens - Maoela, Malebajoa Anicia (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhDConsEcol)--Stellenbosch University, 2015.